2017
DOI: 10.1038/s41467-017-01062-w
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to checkpoint blockade therapy through inactivation of antigen presentation

Abstract: Treatment with immune checkpoint blockade (CPB) therapies often leads to prolonged responses in patients with metastatic melanoma, but the common mechanisms of primary and acquired resistance to these agents remain incompletely characterized and have yet to be validated in large cohorts. By analyzing longitudinal tumor biopsies from 17 metastatic melanoma patients treated with CPB therapies, we observed point mutations, deletions or loss of heterozygosity (LOH) in beta-2-microglobulin (B2M), an essential compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
628
4
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 760 publications
(661 citation statements)
references
References 44 publications
26
628
4
3
Order By: Relevance
“…Among the cancer‐related markers, we observed the expression of β2M, STAT3, STING, and β‐catenin (Figure B). The expression of β2M suggests that tumour antigens are presented via HLA‐A in these tumour areas, thus supporting the efficacy of ICI . Total levels of STAT3 were elevated, but not in its activated phosphorylated form (pY705), which regulates gene transcription for modulation of immunosuppressive factors .…”
Section: Resultsmentioning
confidence: 88%
“…Among the cancer‐related markers, we observed the expression of β2M, STAT3, STING, and β‐catenin (Figure B). The expression of β2M suggests that tumour antigens are presented via HLA‐A in these tumour areas, thus supporting the efficacy of ICI . Total levels of STAT3 were elevated, but not in its activated phosphorylated form (pY705), which regulates gene transcription for modulation of immunosuppressive factors .…”
Section: Resultsmentioning
confidence: 88%
“…12,13,27 Mutations in JAK1 and JAK2 and defects in INF-c signaling have been implicated in resistance to anti-CTLA-4 and anti-PD-1 therapy. 10 Glucocorticoids extensively modify cytokine signaling and can inhibit the interleukin-2 and INF-c pathways. 28 Mutations in b-2 microglobulin also appear to impart resistance to treatment with CTLA-4 and PD-1 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Optimal management strategies for patients with primary hypophysitis and checkpoint inhibitor (CPI)-associated hypophysitis are poorly defined; therefore, treatment patterns, including glucocorticoid dosages, vary. [10][11][12] High doses of glucocorticoids inhibit the immune response, including some pathways linked to CPI resistance. 9 Defects in the immune response are associated with primary and acquired resistance to CPIs.…”
Section: Introductionmentioning
confidence: 99%
“…This group found β2‐microglobulin gene mutations and loss of heterozygosity (LOH) at baseline in a cohort of melanoma samples taken from patients with intrinsic resistance to anti‐CTLA‐4 and anti‐PD‐1 therapy . β2‐microglobulin mutations have commonly been observed enriched in patients with disease relapse . Other study found enriched cellular ( FYB , CXCL9, CD69, CD8A, CARD11 , and CD5 ) and humoral (immunoglobulin heavy chain variants) immune responses in the group with clinical benefit to ipilimumab therapy …”
Section: Genomic Signatures Predicting Response To Anti‐ctla‐4 and Pdmentioning
confidence: 99%